Phytoplankton And Zooplankton Assessment From A Pond In Bhagrana, Fatehgarh Sahib, Punjab, India - Veerpal Kaur; Bhupinderjit Kaur Heer; Mado Sangyu (International Journal of Marine Life, 2024)
The present study was conducted assess of Phytoplankton and zooplankton from a Pond in Bhagrana, Fatehgharh Sahib, Punjab, India. Water samples were collected on a monthly basis, from January 2020 to March 2020, using a ring type terracotta net plankton net (24 meshes/mm2 mesh size) and 50 L were filtered through it to collect plankton sample. For the qualitative analysis, plankton was identified in general. The faunal community was observed to be significantly dominated by phytoplankton. Five Orders of planktons were recorded viz. Chlorophyceae, Euglenophyceae, Bacillariophyceae, Cyanophyceae and Dinophyceae. 19 genera of phytoplankton. The phytoplankton community was dominated by, in the order: Chlorophyceae > Euglenophyceae > Bacillariophyceae > Cyanophyceae > Dinophyceae. Bacillariophyceae, Cyanophyceae and Dinophyceae. Chlorophyceae includes species of Clamydomonas sp., Volvox sp., Sphaerocystis sp., Pediastrum sp., Ankistrodesmus sp., Closterium sp., Cosmarium sp., Oedogonium sp., Ulothrix sp., Scenedesmus sp. Euglenophyceae includes species of Euglena sp. and Phacus sp. Bacillariophyceae includes species of Cyclotella sp. Diatoma spp. and Synedra sp. Cyanophyceae includes species of Microcystis sp., Oscillatoria sp., Nostoc sp. Dinophyceae has been represented by one species i.e. Peridium sp. 9 The zooplankton found consisted of the following species: Copepoda, Rotifera, Cladocera, and Protozoa. The zooplankton community was dominated by parasites, followed by Copepoda, Rotifera, and Cladocera. Protozoa includes species of Amoeba sp., Trinema sp. and Paramecium sp. Rotifera have been represented by Brachionus sp. and Rotaria sp. Cladocera includes Daphnia sp. and Moina sp. Group Copepoda includes Diaptomus sp. and Cyclops sp. . The zooplankton abundance was found to be less during the January and Feb month and only slight increase in almost all the zooplanktons have been observed in month of March.
Keywords: Fish; Monitoring; Phytoplankton; Pond ecosystem; Zooplankton